2018
DOI: 10.1016/j.mex.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

One-phase phenol-free method for microRNA isolation from blood plasma

Abstract: MicroRNA extraction is an essential procedure when discovering MicroRNA-based biomarkers and approaches. Here we describe a new method for microRNA isolation from human blood plasma, based on isopropanol precipitation from the one-phase lysate. We demonstrate that the use of more than four volumes of lysis buffer based on 5 M guanidine isothiocyanate prevents the formation of large, viscous, and hardly soluble precipitate. Applying widely used linear polyacrylamide (LPAA) as the only precipitating agent proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…TRIzol extracted plasma had consistently higher Cq values across multiple miRNA and lower overall RNA recovery. Several more conflicting studies over the application of the gold standard RNA isolation methods to circulating miRNA recovery have been reported, which display favourable results over kit based protocols, suggesting that there is a high degree of variability and operator influence on its success 11,23,24 . Following these reports, commercial kits optimised for biological samples such as plasma and serum which may be used with small sample volumes, are ideal for miRNA profiling and biomarker discovery in archived or clinical samples 11,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…TRIzol extracted plasma had consistently higher Cq values across multiple miRNA and lower overall RNA recovery. Several more conflicting studies over the application of the gold standard RNA isolation methods to circulating miRNA recovery have been reported, which display favourable results over kit based protocols, suggesting that there is a high degree of variability and operator influence on its success 11,23,24 . Following these reports, commercial kits optimised for biological samples such as plasma and serum which may be used with small sample volumes, are ideal for miRNA profiling and biomarker discovery in archived or clinical samples 11,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that phenol-based and combined phenol and column based RNA extraction method efficiently extracted RNA from the sEVs that were lacking cellular RNA content, making it a useful tool for RNA extraction. Therefore, it is postulated that there may be a high variability in RNA concentration due to differences in the species, sample, and state of the host, which influences the kit’s performance and its success [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study used serum and cerebrospinal fluids to compare the commercial kit and TRlzol extraction methods for miRNAs recovery and found that TRlzol isolation techniques have low recovery (34). However, many other studies added suggestions and modifications to the TRlzol extraction methods and improved the recovery of the circulating miRNAs over commercial kits (35)(36)(37). Quantification of the isolated biomarkers can be performed using NanoDrop spectrophotometers.…”
Section: Methods On Isolating Micrornasmentioning
confidence: 99%